The Art of Sinning - Jeffries, Sabrina (New York Pocket Books, 2015)
At St. Georges Club, guardians conspire to keep their unattached sisters and wards out of the clutches of sinful suitors, which works fine--except when the sinful suitors are members.
"Pocket books romance"--Spine.
Keywords: Man-woman relationships -- Fiction; Aristocracy (Social class) -- Fiction; Artists -- Fiction; Americans -- England; London; Fiction; Missing persons -- Fiction; London (England) -- Fiction; Romance fiction